(untitled) (Research, Society and Development, 2021)
This study analyzes the extent to which medical resources for public health in the 80 largest Brazilian municipalities are used efficiently. This research is based on the search for government efficiency, arising from the managerialism developed in the public sector. In this sense, it is assumed that public institutions need their resources economically, maintaining or increasing the quality of services provided. The investigation focuses on 76 cities with data between 2013 to 2017 and measured efficiency through Data Envelopment Analysis (DEA). Health expenses (incomings) and 6 other outgoing variables (outflows) were considered, namely: Hospital Admission Authorization, deaths, days of stay, average value of admissions, value of hospital services and days of admissions. The DEA modeling was developed with input orientation by the BCC model (variable returns to scale). The results of the study demonstrate that the most efficient cities are concentrated in the south and southeast regions. However, the main demonstration of the finding is that only the increase in health expenses does not correspond to more efficient services. The data show that the efficiency obtained is related to the good management of public resources and not necessarily to the volume of administrative resources. It should also be emphasized that public managers can use the municipalities listed in the result as a benchmark for the model, in order to enhance the indicators and improve the management of public resources. Furthermore, the study is advancing the theory in public administration and accounting for social management in the health area.